2014
DOI: 10.1002/chin.201438217
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Antiinflammatory Components of Euphorbia humifusa Willd.

Abstract: Two new compounds, euphorbinoside (I) and dehydropicrorhiza acid methyl ester (II), are isolated from Euphorbia humifusa along with 24 known compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Similarly, the antiinflammatory activity of EHNB was assessed the best, even Frontiers in Pharmacology frontiersin.org when compared to the NSAID indomethacin. Therefore, our finding enhances prior discoveries demonstrating the antiinflammatory of this species through inhibition of soluble epoxide hydrolase (SEH), lipopolysaccharide (LPS)-induced nitric oxide and the tumor necrosis factors (TNF) productions (Luyen et al, 2014). Interestingly, the antioxidant evaluations via DPPH, ABTS and FRAP assays showed the highest potentialities of the EHNB fraction.…”
Section: Potential Ligands Activities Validationssupporting
confidence: 74%
“…Similarly, the antiinflammatory activity of EHNB was assessed the best, even Frontiers in Pharmacology frontiersin.org when compared to the NSAID indomethacin. Therefore, our finding enhances prior discoveries demonstrating the antiinflammatory of this species through inhibition of soluble epoxide hydrolase (SEH), lipopolysaccharide (LPS)-induced nitric oxide and the tumor necrosis factors (TNF) productions (Luyen et al, 2014). Interestingly, the antioxidant evaluations via DPPH, ABTS and FRAP assays showed the highest potentialities of the EHNB fraction.…”
Section: Potential Ligands Activities Validationssupporting
confidence: 74%
“…[14,15] This is because previous reports demonstrated that flavonoids can suppress both pathways of arachidonic metabolism, namely lioxygenase and cyclooxygenase pathways. [17,18] In a separate study, Luyen and his colleagues (19) isolated twenty six compounds from Euphorbia humifusa. [19] Most of these compounds demonstrated anti-inflammatory activities as indicated by their inhibitory effects on soluble epoxide hydrolase, lipopolysaccharide-induced NO and TNF-α production.…”
Section: Discussionmentioning
confidence: 99%
“…[17,18] In a separate study, Luyen and his colleagues (19) isolated twenty six compounds from Euphorbia humifusa. [19] Most of these compounds demonstrated anti-inflammatory activities as indicated by their inhibitory effects on soluble epoxide hydrolase, lipopolysaccharide-induced NO and TNF-α production. In a comparable study, thirteen diterpenoids were isolated from the roots of Euphorbia ebracteolata.…”
Section: Discussionmentioning
confidence: 99%